Stages of sight translation: Evidence from eye movements. (12th September 2022) - Lijewska, Agnieszka; Chmiel, Agnieszka; Inhoff, Albrecht W.
Abstract: The aim of the study was to investigate the coordination of source text comprehension and translation in a sight translation task. The study also sought to determine whether translation strategies influence sight translation performance. Two groups of conference interpreters—professionals and trainees—sight translated English sentences into Polish while their eye movements and performance were monitored. Translation demands were manipulated by the use of either high- or low-frequency critical words in the sentences. Translation experience had no effect on first-pass viewing durations, but experts used shorter re-view durations than trainees (especially in the low-frequency condition). Professionals translated more accurately and with less pausing than trainees. Translation in the high-frequency condition was more accurate and had shorter pauses than in the low-frequency condition. Critical word translation accuracy increased with the translation onset latency (TOL) for individual sentences, and pause durations were relatively short when TOLs were either relatively short or long. Together, these findings indicate that, in sight translation, the initial phase of normal reading for comprehension is followed by phases in which reading and translation co-occur, and that translation strategy and translation performance are linked.